Temporal transcriptional profiling of host cells infected by a veterinary alphaherpesvirus using nanopore sequencing - Dóra Tombácz; Zoltán Maróti; Péter Oláh; Ákos Dörmő; Gábor Gulyás; Tibor Kalmár; Zsolt Csabai; Zsolt Boldogkői (Scientific Reports)
Abstract In our research, we performed temporal transcriptomic profiling of host cells infected with Equid alphaherpesvirus 1 (EHV-1) by utilizing direct cDNA sequencing based on nanopore MinION technology. The sequencing reads were harnessed for transcript quantification at various time points. Viral infection-induced differential gene expression was identified through the edgeR package. The identified genes were segmented into six groups based on their kinetic characteristics. The initial three clusters encompass immediate-early response genes, typically transcription factors and elements of antiviral signaling pathways. These genes were either upregulated (cluster 1) or downregulated (clusters 2 and 3) during the early infection phase. The remaining three clusters include late response genes. In these categories, it is challenging to determine whether changes in gene expression are directly connected to the viral infection or merely side effects of the infection. A study of gene associations using the STRINGDB software revealed several gene networks that might be directly impacted by the virus. We also explored whether gene co-expression could be a result of their collective regulation by upstream transcription factors using the Gene Regulatory Network database. Finally, our differential transcript usage (DTU) analysis identified a number of genes that exhibited altered proportions of transcript isoforms in comparison to non-infected cells. Thus, our analysis revealed that EHV-1 infection not only alters host gene expression but also leads to differential use of transcript isoforms, particularly splice variants.